Etika dan Profesi Guru SD di Tengah Perkembangan Zaman - Siti Fudiana; Indah Salsabila; Nurul Hidayah; Nisrina Alya Salsabila (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid development of the times, marked by technological advances, social changes, and global demands, presents specific challenges for the profession of elementary school teachers. Teachers are not only required to master pedagogical and professional competencies, but also to uphold professional ethics in carrying out their duties as educators. This article aims to examine in depth the ethics and profession of elementary school teachers in the context of contemporary developments through a literature review of relevant books and scientific journals. The method employed is a literature study by analyzing nine sources that discuss the teaching profession, teachers’ codes of ethics, personal ethics, and the challenges faced by teachers in the modern era. The results of the review indicate that professional ethics serve as a fundamental foundation in shaping teachers’ professional attitudes, maintaining the dignity of the teaching profession, and building healthy relationships between teachers, students, and the community. Amid ongoing developments, elementary school teachers are required to adapt to change without abandoning the ethical values established in the teachers’ code of ethics. Therefore, strengthening ethics and professionalism among elementary school teachers is an essential requirement in addressing the challenges of education in the global era.